Observational evidence for enhanced magnetic activity of superflare stars - Karoff, Christoffer; Knudsen, Mads Faurschou; De Cat, Peter; Bonanno, Alfio; Fogtmann-Schulz, Alexandra; Fu, Jianning; Frasca, Antonio; Inceoglu, Fadil; Olsen, Jesper; Zhang, Yong; Hou, Yonghui; Wang, Yuefei; et al. (Nature communications, 2016)
Superflares are large explosive events on stellar surfaces one to six orders-of-magnitude larger than the largest flares observed on the Sun throughout the space age. Due to the huge amount of energy released in these superflares, it has been speculated if the underlying mechanism is the same as for solar flares, which are caused by magnetic reconnection in the solar corona. Here, we analyse observations made with the LAMOST telescope of 5,648 solar-like stars, including 48 superflare stars. These observations show that superflare stars are generally characterized by larger chromospheric emissions than other stars, including the Sun. However, superflare stars with activity levels lower than, or comparable to, the Sun do exist, suggesting that solar flares and superflares most likely share the same origin. The very large ensemble of solar-like stars included in this study enables detailed and robust estimates of the relation between chromospheric activity and the occurrence of superflares. Superflares are large explosive events on stellar surfaces, much larger than solar flares, but it remains unclear whether they share the same origin. Here, the authors analysed 48 superflare stars and determine the relation between their chromospheric activity and the occurrence of superflares.